Aggregatibacter actinomycetemcomitans in periodontal disease, identification through the PCR technique - Orellana Bravo , Paola Patricia (2024)
Objectives: The aim of this article was to investigate the pathogen Aggregatibacter actinomycetemcomitans (A. actinomycetemcomitans) and identify it by polymerase chain reaction (PCR). Materials and methods: The alkaline lysis technique was used for DNA extraction, and a segment of the 16S rRNA gene of A. actinomycetemcomitans was amplified by PCR and specific primers. The specificity of the primers was tested using genetic material extracted from the reference strain A. actinomycetemcomitans ATCC 33384, against other strains. Results: This pathogen was investigated in detail and A. actinomycetemcomitans was identified by means of specific primers. Conclusions: A sensitive and specific technique for the detection of A. actinomycetemcomitans was obtained by conventional PCR.